Uma análise do processo de manutenção de software em organizações de tecnologia da informação - Thomazinho, Hellen Christine Seródio (2018)
Software maintenance is the activity in which changes occur in the artifacts of a software after its delivery, in order to keep it available, correct its faults improve its performance and adapt it to new or modified requirements, according to the needs of your users. It is an essential activity, without which existing systems would quickly become lagging and inefficient for organizations. In this context, the objective of this work is to perform an analysis of the software maintenance process in organizations of the productive sector and present a model of maintenance process. In this sense, the purpose is to support organizations, which develop software in the identification of the elements that make up a maintenance process and promote, improvements in planning and execution of activities. To achieve this objective, a hybrid method was applied, consisting of experiments and multiple case studies, both with the purpose of validating the model presented in this work. The experiments demonstrated that it was possible to validate the preliminary model and measure the learning capacity of teams in the application of processes and activities related to software maintenance. The results obtained from the case studies showed that organizations do not follow a single maintenance model and that the greatest demand is for corrections and adaptations. In addition, strategies associated with knowledge management of the user and the development / maintenance team are relevant to increase the effectiveness of the maintenance process. In this way, it is expected that such model will be adherent in any organization of the productive sector, whether or not it is certified by some quality model.